Klenikologi: World Charm and Fine Dissident Among Javanist Received by Trust - Endraswara, Suwardi (Javanologi: International Journal of Javanese Studies, 2017)
Klenikologi derived from the word heresy and logy. Klenikologi is knowledge (ngelmu) about perklenikan kejawen. Heresy is kejawen movement "under ground", which actually has incredible powers. Occult spells can not be separated from the universe. Mantra comes from the word "man" (whispered tool) and "tra" means the appliance. Mantra is a tool in a whisper, to "direct communication" with Kang Akarya Universe. Klenikologi kejawen really lungit (sacred and fine), not everyone is able to reach them. Only someone who has buntas kawruhe and meneping flavor, usually capable of using klenikologi kejawen. Klenikologi kejawen genuine (original), will use spells kejawen. In the life received by faith kejawen, klenikologi and spells always have a special function and meaning. First, klenikologi and magical spells as the opener of the universe, to be mystically connected with Kang Murbeng Dumadi (God). Mantra, usually in the form of sacred chants, sung by a trusted person physically and spiritually. Second, kenikologi and spells that are used as motion "dissident smooth", in a government policy diametrically opposed to him. Third, klenikologi and spells to deny custody, the interference jim priprayangan devil, breakfast convulsions, and other temptations. Fourth, klenikologi and spells for tapa ngrame, namely helping sesameng dumadi, who need help. From the description, may I suggest that klenikologi, spells, and "subtle dissident" received by the trust among the Javanese, is a phenomenon that has a sacred meaning. To take advantage of this phenomenon requires special training and behavior. This phenomenon was a resistance of the entire policy beliefs sometimes (a) oppressive, (b) does not solve the problem, (c) is irrelevant between reality and rules. That is why received by trying to find "alternative path", which is more reassuring to live.